Empowering Teachers Through Innovation: Professional Development for 21st-Century Education - Irma Suryani (PT Mutiara Bustan Ilmu, 2024)
This study explores the effectiveness of constructivist and traditional approaches in teaching Arabic to beginners. The constructivist approach, grounded in active learning and real-world application, emphasizes learner engagement and collaborative learning. The traditional approach, however, focuses on structured grammar-based instruction, providing learners with a foundational understanding of language rules. Through a comparative analysis of two groups of beginners.